2012
DOI: 10.1103/physrevb.86.045315
|View full text |Cite
|
Sign up to set email alerts
|

Cavity quantum electrodynamics with a single quantum dot coupled to a photonic molecule

Abstract: We demonstrate the effects of cavity quantum electrodynamics for a quantum dot coupled to a photonic molecule consisting of a pair of coupled photonic crystal cavities. We show anti-crossing between the quantum dot and the two super-modes of the photonic molecule, signifying achievement of the strong coupling regime. From the anti-crossing data, we estimate the contributions of both mode-coupling and intrinsic detuning to the total detuning between the super-modes. Finally, we also show signatures of off-reson… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 31 publications
(49 reference statements)
2
77
0
1
Order By: Relevance
“…We note that the mean µ of the mode separations is a combination of the coupling strength and the disorder, whereas the standard deviation σ of the mode separations depends mostly on the disorder, as explained earlier. To elaborate further, we can consider the simple example of a photonic molecule (two coupled cavities), where the observed separation ∆ between two modes is ∆ 2 0 + 4J 2 with ∆ 0 being the random bare detuning between the cavities due to fabrication imperfection and J being the the coupling strength [16]. We assume that the bare detuning follows a Gaussian probability distribution with zero mean and standard deviation σ f , i.e., the probability of having a detuning ∆ 0 is…”
Section: Spectra Of Coupled Cavitiesmentioning
confidence: 99%
“…We note that the mean µ of the mode separations is a combination of the coupling strength and the disorder, whereas the standard deviation σ of the mode separations depends mostly on the disorder, as explained earlier. To elaborate further, we can consider the simple example of a photonic molecule (two coupled cavities), where the observed separation ∆ between two modes is ∆ 2 0 + 4J 2 with ∆ 0 being the random bare detuning between the cavities due to fabrication imperfection and J being the the coupling strength [16]. We assume that the bare detuning follows a Gaussian probability distribution with zero mean and standard deviation σ f , i.e., the probability of having a detuning ∆ 0 is…”
Section: Spectra Of Coupled Cavitiesmentioning
confidence: 99%
“…1. This system can be realized in nanocavities, using micropillars [38][39][40] , microdiscs 41 , and photonic crystals (PhCs) [42][43][44][45] . Cavity resonance frequencies (ω 1 and ω 2 for cavity 1 and cavity 2, respectively) are tuned close to the QD-biexciton two-photon resonance,…”
Section: A Preparation Of 2002-ges In Qd-coupled-cavity Systemsmentioning
confidence: 99%
“…by temperature tuning technique 32,52 and by xenon gas deposition technique 53 . Tunneling parameter J depends on a distance between cavities, meV order for direct coupling 42 and tens of µeV for waveguide mediated coupling 43 . Especially for the latter case, J is electrically controllable 54 with high precision in a range of µeV, using an extra control cavity 55 .…”
Section: A Preparation Of 2002-ges In Qd-coupled-cavity Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have demonstrated that a photonic molecule can solve this problem 5 . A photonic molecule is composed of two cavities coupled by a fast photon tunneling interaction [3][4][5][6][7] . These photonic structures exhibit two non-degenerate modes, one that strongly couples to the quantum dot and a second that can induce a cavity-enhanced AC Stark effect.…”
Section:     mentioning
confidence: 99%